Effects of Yeast Culture Supplementation in Wheat–Rice-Based Diet on Growth Performance, Meat Quality, and Gut Microbiota of Growing–Finishing Pigs - Yan Lin; Chenglong Yu; Zhao Ma; Lianqiang Che; Bin Feng; Zhengfeng Fang; Shengyu Xu; Yong Zhuo; Jian Li; Junjie Zhang; Min Yang; Peng Chen; et al. (Animals, 2022)
The aim of this study was to investigate the effects of yeast culture (Saccharomyces cerevisiae) supplementation on the growth performance, meat quality, gut health, and microbiota community of growing–finishing pigs. A total of 45 growing–finishing pigs were randomly allocated to three treatments: a corn–soybean-based diet (CON, n = 15), a wheat–rice-based diet (GRA, n = 15), and GRA supplemented with 500 mg/kg yeast culture (YC, n = 15). The results show that compared to the CON group, the GRA group exhibited no significant differences in feed intake, daily gain, or feed conversion ratio, but had significantly reduced feed cost per kilogram BW gain of the finishing pigs (p < 0.05). Compared to that of the CON group, the GRA and YC groups showed an increase in the dressing percentage (p < 0.1). The meat color redness of the YC group increased (p < 0.1), whereas the b* value at 24 h decreased (p < 0.1). Meanwhile, the addition of YC significantly increased total superoxide dismutase activity on day 30 and catalase activity on day 60 (p < 0.05), and decreased serum urea nitrogen content on day 60 (p < 0.05). Furthermore, YC supplementation increased the gene expression of the duodenal anti-inflammatory factor IL-10 (p < 0.05), while it significantly decreased the gene expression of the ileal pro-inflammatory factor IL-8 (p < 0.05). The intestinal microbial identification results show that compared to the CON group, the YC group showed an increase in the relative abundances of Lactobacillus, Streptococcus, and Clostridium in the colon, and a decrease in the relative abundances of Bacteroidea, Clostridae, and Prevotella in the cecum. In conclusion, the growth performance of pigs on a wheat–rice-based diet was similar to that of pigs on a corn–soybean-based diet. Supplementation of 0.5% YC in the wheat–rice-based diet could improve the dressing percentage and meat color of growing–finishing pigs, which might be due to the increase in nitrogen utility and antioxidant capacity, and the improvement of the immune system and changes in microbiota communities.